Copper-based intersectional nanofabrication of optical nanoantennas for volatile organic compound sensing - Meng Li; Yan Huang; Lipeng Sun; Zhaoqiang Zheng; Churong Ma; Xiangping Li; Bai-Ou Guan; Kai Chen (APL Photonics, 2023)
Plasmonic sensors leverage the enhanced near-fields associated with the constituent optical nanoantennas to achieve better sensing performance. The design and fabrication of these optical nanoantennas, especially metallic ones, are thus becoming critical steps to advance this thriving and important field. Low-cost and high-throughput nanofabrication techniques are greatly desirable. In this work, we demonstrate a cost-effective nanofabrication method derived from conventional colloidal lithography. With polystyrene nanospheres and subsequently formed copper (Cu) nanoholes as consecutive deposition masks, disk nanoantennas can be produced in a large-scale fashion with no dry etching required. Furthermore, the nanodisks can be readily tuned via thermal heating of the sacrificial Cu nanohole layers. Finally, we combined the fabricated Au nanodisks with the metal-organic framework material zeolitic imidazolate framework-8 and demonstrated highly sensitive detection of volatile organic compounds. We believe that this nanofabrication method could be readily implemented in a variety of plasmonic sensors.